2023
DOI: 10.1617/s11527-023-02133-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of hydrated cement powder by thermal treatment for partial replacement of ordinary portland cement

Abstract: Cement is the strength-forming component of concrete. It has been a major building material for more than a century. However, its production is accountable for a considerable percentage of global CO2 emissions and is very energy-intensive. The Ordinary Portland Cement (OPC) production is a thermal process at around 1450 °C. This study shows that the reactivation of Hydrated Cement Powder (HCP) can be successful at a much lower temperature. Therefore, the possibility of using HCP to replace parts of OPC in conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This becomes clear by analyzing the peaks that occur at 27 • and 33 • . In addition, the peaks related to hydrated calcium silicate, which is mainly responsible for cement strength [43], are less intense for the NaOH composition, as observed in the peak at 30 • . The identification of CSH is possible through Rietveld refinement, since CSH is a compound with low crystallinity, according to the methodology defined in other studies [44].…”
Section: Comparison Between Reference and Coffee Husk Mortars Treated...mentioning
confidence: 94%
See 1 more Smart Citation
“…This becomes clear by analyzing the peaks that occur at 27 • and 33 • . In addition, the peaks related to hydrated calcium silicate, which is mainly responsible for cement strength [43], are less intense for the NaOH composition, as observed in the peak at 30 • . The identification of CSH is possible through Rietveld refinement, since CSH is a compound with low crystallinity, according to the methodology defined in other studies [44].…”
Section: Comparison Between Reference and Coffee Husk Mortars Treated...mentioning
confidence: 94%
“…These results explain the compressive strength values obtained at 28 days, where it was observed that the reference composition and the KOH composition present equivalent strengths, while the NaOH mortar composition presents statistically lower compressive strength. This happened due to the non-formation of phases such as C-S-H and portlandite, responsible for the strength of the cement [43], and due to the NaOH content having acted as a retardant in the hardening process of the material.…”
Section: Comparison Between the Reference Mortars And Those With Natu...mentioning
confidence: 99%
“…However, cementitious material production not only affects construction but also greenhouse gas emissions and natural resource depletion (Hossain et al, 2021). There is a signi cant surge in CO 2 emissions from cement production, which is becoming expensive due to its energy-intensive production process, and certain countries are already experiencing shortages of the essential components (Danish et al, 2021; Ritchie et al, 2020; Semugaza et al, 2023). Cement production is a major contributor to CO 2 emissions and environmental issues (C. Chen et al, 2022;Mahasenan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%